2022
DOI: 10.1093/nar/gkac037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of guanidine-containing backbone linkages on stereopure antisense oligonucleotides in the CNS

Abstract: Attaining sufficient tissue exposure at the site of action to achieve the desired pharmacodynamic effect on a target is an important determinant for any drug discovery program, and this can be particularly challenging for oligonucleotides in deep tissues of the CNS. Herein, we report the synthesis and impact of stereopure phosphoryl guanidine-containing backbone linkages (PN linkages) to oligonucleotides acting through an RNase H-mediated mechanism, using Malat1 and C9orf72 as benchmarks. We found that the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…Overall, these data indicate that WVE-004 does not induce cytotoxicity and that it induced relatively low cytokine production compared with the positive control in vitro at the concentrations tested in this assay. WVE-004’s impact on PBMC cytokine secretion is consistent with our prior report that PN-modified oligonucleotides are not pro-inflammatory and may be less inflammatory than a PS-modified counterpart, 45 which may be critical if the C9orf72 -repeat expansion leads to a pro-inflammatory state. 34 , 35 …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, these data indicate that WVE-004 does not induce cytotoxicity and that it induced relatively low cytokine production compared with the positive control in vitro at the concentrations tested in this assay. WVE-004’s impact on PBMC cytokine secretion is consistent with our prior report that PN-modified oligonucleotides are not pro-inflammatory and may be less inflammatory than a PS-modified counterpart, 45 which may be critical if the C9orf72 -repeat expansion leads to a pro-inflammatory state. 34 , 35 …”
Section: Resultssupporting
confidence: 89%
“…It contains a combination of stereopure PS and PN linkages, which we have previously shown can improve potency, distribution, and durability compared with similar PS-modified antisense oligonucleotides in the CNS. 45 Herein, we reinforce these findings by showing that WVE-004 can lead to sustained reductions in V3 transcripts and poly-GP in the spinal cord and cortex for at least 6 months. To our knowledge, this long-term effect with a relatively low dose is unprecedented in the CNS of mouse models.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, it has been shown that the incorporation of PN linkages into stereopure oligonucleotides with chimeric backbone modifications has the potential to render regions of the brain beyond the spinal cord more accessible to oligonucleotides and, consequently, may also expand the scope of neurological indications amenable to oligonucleotide therapeutics. Incorporation of various types of PN linkages to a stereopure oligonucleotide backbone can increase the potency of silencing in cultured neurons under free-uptake conditions 10-fold compared with similarly modified stereopure phosphorothioate (PS)- and phosphodiester (PO)-based molecules …”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of various types of PN linkages to a stereopure oligonucleotide backbone can increase the potency of silencing in cultured neurons under free-uptake conditions 10-fold compared with similarly modified stereo-pure phosphorothioate (PS)-and phosphodiester (PO)-based molecules. 16 Recently, the advantages of PN applications in an allelespecific real-time PCR analysis have been shown. The introduction of phosphorylguanidine modification(s) leads to a significant increase in the selectivity and a decrease in the concentration detection limit of the mutant DNA.…”
Section: Introductionmentioning
confidence: 99%